A uniform procedure of a system resources interaction in distributed computer media - Listrovoy, Serhiy Volodymyrovych; Trubchaninova, Karyna Arturivna; Bryksin, Volodymy Oleksandrovych; Kurtsev, Maksym Serhiyovych (NTU "KhPI", 2017)
Nowadays railways present the processes of the existing information systems and their integration into a uniform automated control system of railway freight transportation. These processes must be based on the uniform architecture, system construction which takes into account current and future information technologies such as grid technologies and cloud calculation technologies. One of the main problems of introducing these technologies is the increased time while planning resources distribution when fulfilling tasks, that appear in distributed control system. It is important to develop uniform approaches to the solution of this problem. A uniform procedure of all the resources interaction that allows organising planning tasks in distributed computer systems in the given article. The procedure of resources distribution on the base on the principle of task distribution and cluster sampling method has been also described.

Детально описана процедура розподілення ресурсів на основі принципу роздільного розподілення задач та на основі методу групової вибірки. Запропонована процедура взаємодії усіх ресурсів, яка дозволяє організувати процес планування виконання завдань в розподілених обчислювальних системах. Також запропонована уніфікована процедура організації взаємодії усіх ресурсів розподіленої обчислювальної системи, яка дозволяє з єдиних позицій організувати процес планування.
Уніфікована процедура організації взаємодії ресурсів системи в розподілених обчислювальних середовищах
Keywords: distributed computing systems; scheduling; task allocation; resource allocation; розподілені обчислювальні системи; планування; розподілення завдань; розподілення ресурсів